2014
DOI: 10.3389/fnsys.2014.00016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-motor interactions of the basal ganglia in development

Abstract: Neural circuits linking activity in anatomically segregated populations of neurons in subcortical structures and the neocortex throughout the human brain regulate complex behaviors such as walking, talking, language comprehension, and other cognitive functions associated with frontal lobes. The basal ganglia, which regulate motor control, are also crucial elements in the circuits that confer human reasoning and adaptive function. The basal ganglia are key elements in the control of reward-based learning, seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 101 publications
(126 reference statements)
5
173
0
5
Order By: Relevance
“…Recent evidence confirms that the basal ganglia, specifically the caudate nucleus, interact closely with the executive parts of frontal lobes to regulate cognitive function. 21 In addition, basal ganglia are essential elements of linguistic learning in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence confirms that the basal ganglia, specifically the caudate nucleus, interact closely with the executive parts of frontal lobes to regulate cognitive function. 21 In addition, basal ganglia are essential elements of linguistic learning in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The PFC has both direct and indirect connections with the amygdala (Carmichael and Price, 1995; Freese and Amaral, 2009; Ghashghaei et al, 2007; Ray and Zald, 2012) and can inhibit amygdala responses (Quirk et al, 2003; Rosenkranz and Grace, 2002). Finally, The basal ganglia are involved in reward processing (Haber and Knutson, 2009; Nestor et al, 2010; Pizzagalli, 2014; Treadway and Zald, 2013; Volkow et al, 2013) and cognitive functioning, including inhibitory control(Leisman et al, 2014). Importantly, the amygdala, prefrontal cortex, and basal ganglia are structurally and functionally interconnected; therefore, it is likely that these three regions form the basis of a neural circuit subserving inhibited temperament (see section 2.4.…”
Section: Neural Basis Of Inhibited Temperamentmentioning
confidence: 99%
“…Second, in their attentional control task, Jarcho and colleagues (2014) found that inhibited individuals had increased activation during attentional control to fear stimuli in the caudate and ventral striatum, and decreased activation during attention control in the happy condition in the putamen. While the basal ganglia have traditionally been ascribed a role in motor control and reward processing, these subcortical brain regions are strongly connected to multiple PFC regions (Di Martino et al, 2008; Haber, 2003; LehĂ©ricy et al, 2004), forming fronto-striatal loops that subserve attention, learning, executive control and cognition (Leisman et al, 2014). Thus, increased activation of basal ganglia regions during both reward anticipation and cognitive control tasks may reflect inhibitory control functions of both the basal ganglia and PFC.…”
Section: Neural Basis Of Inhibited Temperamentmentioning
confidence: 99%
“…The left superior temporal gyrus (see Graves, Grabowski, Mehta, & Gupta, 2008) and the basal ganglia (for a review, see Ullman, 2004) are also implicated in lexical and phonological processing. Furthermore, the basal ganglia are strongly connected to the frontal cortex (see Ullman, 2004), to the extent that lesions in these structures may resemble deficiencies from frontal cortex damage (Leisman, Braun-Benjamin, & Melillo, 2014). Our results regarding the neural correlates of increased gesture production support the idea that people use more gestures to compensate for their language impairment.…”
Section: Discussionmentioning
confidence: 99%